Pengaruh Menyikat Gigi dengan Kombinasi Pasta Gigi dan Siwak (Salvadora persica) terhadap Jumlah Koloni Bakteri Anaerob pada Saliva dan Mukosa Gingiva Santri Ar-Razi - Catur Eka Sukma; Helmin Elyani; Arif Yahya (Jurnal Kedokteran Komunitas, 2020)
Background: Anaerobic bacteria in oral cavity have the potential for health in the oral cavity and also systemic. Sodium Lauryl Sulfat (SLS) and fluoride in toothpaste as an antibacterial. Benzyl isothiocyanate (BITC) in siwak has antibacterial activity. This study aim to prove the effect of combination siwak and toothpaste towards anaerobic bacteria in saliva and mucosal gingiva.Method: This research was experimental laboratory with pre and post test group design. A total of 36 respondents were divided into 2 groups, brushing using toothpaste and brushing using a combination of toothpaste and siwak during 10 days. Samples of saliva and gingival mucosa were taken before and after treatment and was grown on Anaerobic Nutrient Agar (NA) media. Data of before and after treatment were analyzed using paired t-test.Result: In group using toothpaste only after treatment increased the amount of anaerobic bacteria in saliva by 34% and decreased in gingiva by 53%. In group using the combination toothpaste and siwak after treatmenct increased the amount of anaerobic bacteria in saliva by 36% and decreased in gingiva by 33%.Conclusion: The combination of brushing using siwak and toothpaste for 10 days can reduce the amount of anaerobic bacteria in gingival samples.Keywords: Siwak, toothpaste, anaerobic bacteria